Modeling myopia: Application to non-renewable resource extraction - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2013)
We develop a parsimonious model of myopia with an infinitesimal period of commitment as an extension to a standard dynamic optimization in a continuous-time environment. We clearly distinguish the processes of planning future controls and choosing the current control, which makes the model both analytically and numerically convenient. In its application to a simple non-renewable resource extraction problem, we show that whether the terminal time is free or fixed determines the appropriateness of the approximation to myopic agents by constant discounting. We also show that the expiry of extraction permits may be useful in the presence of myopia.